The Terrorist Project in Terms of the Agreement - Yassin, Ali; Hussein, Alaa (Journal of Legal Sciences, 2023)
Terrorist crime is considered a serious act that outweighs all other crimes in terms of impact and result, because it has a wide range on societies, and it also contains a great thing of danger represented in its purpose, and here describing terrorism as a crime is a description that does not give the full right to this behavior or that it It abbreviates it and does not show its actual reality, given that terrorism contains several different crimes and the roles of its contributors, and these roles are necessary to reach the result or the end. In which each episode is complementary to the other, it is not a single act, but rather several joint and complex actions that in turn all lead to the result, and the agreement in the terrorist project begins when agreeing on the formation of the project, and thus the intention and intent is available in its formation and the path to its goal, and therefore, the agreement cannot be considered On the project, it is a consequential contribution as in other crimes, except for the agreement on state security crimes, which the legislator considered an independent crime by mere agreement, even if the crime did not occur and ignored for the people The terrorist threat, therefore, the agreement is an independent act and an existing crime and an original actor who did not commit it even if the crime did not occur, because the danger of the terrorist crime is not less than the seriousness of the state security crimes, but rather it is more dangerous because it is related to society and its change and its connection to belief and thought, so the agreement is in the terrorist project It is a crime for which the law is held accountable, even if it did not occur.